Tradisi Tedhak Siten di Masyarakat Desa Penggalangan, Tebing Syahbandar, Serdang Bedagai: Aspek Nilai Sosial dan Budaya - Muslimah, Ikhwatun; Yuniarti, Yuniarti; Br. Perangin-Angin, Alemina (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
The tradition of tedhak siten holds great significance within Javanese culture, symbolizing a baby's journey from birth. This ritual not only celebrates the baby's arrival and well-being but also serves as a means to protect against seizures. Embedded within the tradition are profound social and cultural values, which are meticulously upheld in Penggalangan Village, Tebing Syahbandar, Serdang Bedagai, renowned for its preservation of this custom. This study meticulously documents the intricate tedhak siten process alongside the social and cultural values ingrained within the community of Penggalangan Village. The primary objective of this research is to comprehensively understand both the ritual itself and the values it embodies. Employing a methodological approach that encompasses interviews, field observations, and extensive literature review, the study delves into the various stages of the tedhak siten procession. These include stepping on 7-colored jenang, ascending a rattan ladder, entering a chicken coop, selecting a cherished object, gathering coins, undergoing a scented water bath, and donning new attire. Among the values reflected throughout the tradition are self-assurance, magnanimity, the preservation of familial dignity, and industriousness.